Looking for New Polycrystalline MC-Reinforced Cobalt-Based Superalloys Candidate to Applications at 1200°C - Patrice Berthod (Advances in Materials Science and Engineering)
For applications for which temperatures higher than 1150°C can be encountered the currently best superalloys, the γ/γ′ single crystals, cannot be used under stress because of the disappearance of their reinforcing γ′ precipitates at such temperatures which are higher than their solvus. Cobalt-based alloys strengthened by refractory and highly stable carbides may represent an alternative solution. In this work the interest was focused on MC carbides of several types. Alloys were elaborated with atomically equivalent quantities in M element (among Ti, Ta, Nb, Hf, or Zr) and in C. Script-like eutectic TiC, TaC, NbC, HfC, and ZrC carbides were successfully obtained in the interdendritic spaces. Unfortunately, only one type, HfC, demonstrated high morphological stability during about 50 hours at 1200°C. The concerned alloy, of the Co-25Cr-0.5C-7.4Hf type (in wt.%), was further characterized in flexural creep resistance and air-oxidation resistance at the same temperature. The creep behaviour was very good, notably by comparison with a more classical Co-25Cr-0.5C-7.5Ta alloy, proving that the interest of HfC is higher than the TaC one. In contrast the oxidation by air was faster and its behaviour not really chromia-forming. Significant improvements of this chemical resistance are expected before taking benefit from the mechanical superiority of this alloy.